2014
DOI: 10.1111/tct.12156
|View full text |Cite
|
Sign up to set email alerts
|

Simulation training for geriatric medicine

Abstract: Simulation is an exciting and novel method of delivering teaching for specialist trainees in geriatric medicine. This teaching modality could be integrated into the training curriculum for geriatric medicine, to allow a wider application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Soon, once worked this aspect, the simulation was becoming a very valuable training modality, which could also be better leveraged with the increase in the use of feedback with video sessions and individual enlightenment. 16 Braude et al, 17 also identified that the majority of the answers of the tests applied in their study were related to the non-technical skills, which were best taught in this modality of teaching. These non-technical skills were divided into four main groups: communication, clinical knowledge, knowledge of the situation and planning, and teamwork.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Soon, once worked this aspect, the simulation was becoming a very valuable training modality, which could also be better leveraged with the increase in the use of feedback with video sessions and individual enlightenment. 16 Braude et al, 17 also identified that the majority of the answers of the tests applied in their study were related to the non-technical skills, which were best taught in this modality of teaching. These non-technical skills were divided into four main groups: communication, clinical knowledge, knowledge of the situation and planning, and teamwork.…”
Section: Discussionmentioning
confidence: 96%
“…24 The skills addressed to the training with simulation in geriatrics are skills of manual skill, effective communication with patients and family members, decision-making, leadership, use of resources, teamwork and empathy. 10, [16][17][18][19][20][21] To discuss the competencies, Gonçalves, Coutinho and Lobão 11 asserting that between the simulation and the development of skills there is a close relationship, because the benefits related to their educational potential, security, costs and results is becoming legitimized by research. Such skills enrich the knowledge in identifying, understanding and resolution of complex hardships stemming from situations that are exposed to students during their practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the article ‘ Simulation training for geriatric medicine’ that appeared in August 2014 issue of The Clinical Teacher, the order of names in the author list was incorrect. The correct order should be: Mehdi Z, Ross A, Reedy G, Roots A, Ernst T, Jaye P, Birns J.…”
mentioning
confidence: 99%